2017
DOI: 10.1016/j.pedhc.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study of Foster Caregivers' Views on Adherence to Pediatric Appointments

Abstract: The current study is a qualitative investigation of how foster caregivers, primarily Latinos, view adherence to pediatric appointments with the purpose of identifying how the child welfare system, pediatric clinics, and pediatric health providers serving foster children might promote appointment attendance. Participants in the study had a return appointment at an outpatient pediatric clinic that only served children in the child welfare system. Twenty-eight caregivers (13 related and 15 unrelated) participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 24 publications
0
21
2
Order By: Relevance
“…Transportation support was noted as a facilitator to appointment keeping in two previous qualitative studies (Cameron et al, 2014; Schneiderman et al, 2017); however, the specific findings within the general category of transportation were different from our findings. Schneiderman et al (2017) identified ease of parking, and having a car as facilitators, while Cameron et al (2014) identified improved transport links as a facilitator.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Transportation support was noted as a facilitator to appointment keeping in two previous qualitative studies (Cameron et al, 2014; Schneiderman et al, 2017); however, the specific findings within the general category of transportation were different from our findings. Schneiderman et al (2017) identified ease of parking, and having a car as facilitators, while Cameron et al (2014) identified improved transport links as a facilitator.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, two previous qualitative studies, which also identified facilitators, focused on how parents themselves could facilitate attendance by addressing the competing priorities of the child and family. These two studies also identified that parents' motivation to "improve the health of their child" facilitated appointment keeping (Cameron et al, 2014;Schneiderman et al, 2017). In addition, health care professionals were interviewed in one study where they suggested that educating parents about the importance of attending appointments and consequences of nonattendance could influence attendance (Cameron et al, 2014).…”
Section: Appointment Keeping Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, post-treatment appointments are usually given at 1 year. Such long appointments are associated with high rates of forgetfulness 31,32. Reminder phone calls, which emerged as a solution to this barrier, have been found to be effective 33,34.…”
Section: Discussionmentioning
confidence: 99%